Insights Gained Into the Treatment of COVID19 by Pulmonary Surfactant and Its Components - Li, Dan; Wang, Xianzheng; Liao, Yingzhao; Wang, Shouchuan; Shan, Jinjun; Ji, Jianjian (Frontiers in Immunology, 2022)
Pulmonary surfactant constitutes an important barrier that pathogens must cross to gain access to the rest of the organism via the respiratory surface. The presence of pulmonary surfactant prevents the dissemination of pathogens, modulates immune responses, and optimizes lung biophysical activity. Thus, the application of pulmonary surfactant for the treatment of respiratory diseases provides an effective strategy. Currently, several clinical trials are investigating the use of surfactant preparations to treat patients with coronavirus disease 2019 (COVID-19). Some factors have been considered in the application of pulmonary surfactant for the treatment COVID-19, such as mechanical ventilation strategy, timing of treatment, dose delivered, method of delivery, and preparation utilized. This review supplements this list with two additional factors: accurate measurement of surfactants in patients and proper selection of pulmonary surfactant components. This review provides a reference for ongoing exogenous surfactant trials involving patients with COVID-19 and provides insight for the development of surfactant preparations for the treatment of viral respiratory infections.